2020
DOI: 10.1061/(asce)ae.1943-5568.0000434
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Construction Virtual Reality Game on Design Review Skills of Construction Students

Abstract: Being able to perform an effective design review is a fundamental skill that every design or construction student should possess. Performing a design review requires critical thinking, analysis, and communication skills. To support the acquisition of these skills, this study investigated the impact of a virtual reality game, the design review simulator (DRS), in a classroom environment. To assess the impact of the game, the authors performed a crossover experiment with 120 students. The students were split int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…VR has been uitlized to assessing the effect of a biophilic environment on users through setting three VR office spaces with different outdoor features, revealing the negative impact of dull spaces on stress levels (Yin et al 2020). Also, it has been used to study the impact of a construction design review skills of construction students (Kandi et al 2020), while considering the thermal, emotional, and cognitive effect of external view existance in VR, allowing comprehensive assessment of the positive impact of windows to space users. These studies succeded in assessing and measuring human behaviour in response to variable stimuli in VR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…VR has been uitlized to assessing the effect of a biophilic environment on users through setting three VR office spaces with different outdoor features, revealing the negative impact of dull spaces on stress levels (Yin et al 2020). Also, it has been used to study the impact of a construction design review skills of construction students (Kandi et al 2020), while considering the thermal, emotional, and cognitive effect of external view existance in VR, allowing comprehensive assessment of the positive impact of windows to space users. These studies succeded in assessing and measuring human behaviour in response to variable stimuli in VR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results demonstrated that the educational simulation game helped students to identify a higher number of design mistakes compared to doing the same task with a paper-based documentation. Working on the same topic and extending it, Kandi et al (2020b) analyzed the order in which students accessed the information and they demonstrated how students that played the game after performing 2D drawing reviews scored significantly higher in the knowledge test. Based on their results, the game could be therefore implemented in an integrated manner with traditional representation.…”
Section: Results From Previous Studies In Terms Of Vr Impact On Learningmentioning
confidence: 99%
“…What emerges from the analysis of the retrieved papers is that often both the research methods and the rationale are unclear, with no clear learning processes defined. The type of learning approach and its correlation with VR implementation is not discussed, as well as the effect from the order of the learning approaches is not observed except in Kandi et al (2020b). In addition, the applications described in the retrieved papers are often under development and interim results are usually discussed, not providing a full-scale implementation to assess learning.…”
Section: Methodological Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rapid development of virtual reality technology, researchers have begun to focus on the application of virtual learning environment, trying to use this environment to promote the formation and development of critical thinking of college students,Kandi et al ( 2020) used an experimental study to nd that students taking architecture courses in a virtual learning environment could improve their design, review, and innovation skills. Also, the study found that a virtual reality game design simulator supported students to identify more design errors and perform better on subsequent critical thinking tests [40] .Kang (2020) developed a virtual reality nursing course and found that it facilitated students' critical thinking development and independent learning skills [41] . However, problems such as high cognitive load and information disorientation are also faced during the use of virtual learning environments, so it is more important to better design virtual learning environments to promote the development and enhancement of critical thinking among college students.…”
Section: No Signi Cant Effect Of Vr Technology In Improving the Level...mentioning
confidence: 99%